2020
DOI: 10.51248/.v40i3.38
|View full text |Cite
|
Sign up to set email alerts
|

A study to compare the effects of aerobic exercises and yoga on depression and maternal anxiety orienting among primiparous women

Abstract: Introduction and Aim: Primiparous women undergo stages of depression or anxiety during pregnancy especially the risk of preterm birth, breast-feeding problems and disruption of the mother-infant attachment. It is a most common psychiatric disorder and is associated with a greater risk of low fetal quality, Pregnancy complication and developmental disorder of the child. During pregnancy 10-15% women were affected with depression and the incidence increases in low economic status. It is associated with greater r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The characteristics of the included studies according to the FITT principle of exercise prescription are described (Table 1 ). Thirteen of the included studies originated from India [ 13 , 28 – 39 ] eight from the USA [ 8 , 11 , 40 45 ], three from Iran [ 46 48 ], two each from China [ 49 , 50 ] and Indonesia [ 51 , 52 ] and one each from Japan, Thailand and the UK [ 53 55 ]. Twenty-five of the studies were RCTs, three were non-randomised control trials and three were a true-experimental post-test only control group design.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The characteristics of the included studies according to the FITT principle of exercise prescription are described (Table 1 ). Thirteen of the included studies originated from India [ 13 , 28 – 39 ] eight from the USA [ 8 , 11 , 40 45 ], three from Iran [ 46 48 ], two each from China [ 49 , 50 ] and Indonesia [ 51 , 52 ] and one each from Japan, Thailand and the UK [ 53 55 ]. Twenty-five of the studies were RCTs, three were non-randomised control trials and three were a true-experimental post-test only control group design.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-five of the studies were RCTs, three were non-randomised control trials and three were a true-experimental post-test only control group design. Twenty studies were conducted with normal healthy pregnant women [ 8 , 13 , 29 31 , 34 36 , 38 , 43 , 46 55 ], two with multi-factor high-risk pregnant women [ 28 , 32 ], six with pregnant women with depression or symptoms of depression [ 11 , 39 42 , 44 ], one with pregnant women with gestational diabetes [ 33 ], one with pregnant women with mild hypertension [ 37 ] and one with high-risk pregnant women on bedrest [ 45 ]. The gestational age at recruitment across studies ranged from 12 to 36 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Warm compress therapy involves applying a compress filled with warm water to the painful area, which can help to reduce dysmenorrhea pain by facilitating blood flow, oxygen supply, and muscle relaxation [3]. Research has shown that warm compress therapy can significantly reduce dysmenorrhea pain [4], and regular exercise can also help [5]. In Indonesia, many young women rely on traditional medicine to treat dysmenorrhea [6], and education about menstruation and available treatments is crucial [7].…”
Section: Introductionmentioning
confidence: 99%